PEDAGOGICAL FACTORS AFFECTING THE PHYSICAL DEVELOPMENT OF PRIMARY SCHOOL CHILDREN - Khamrokulov Rasul Abdusattorovich; Nuriddin Muradovich Karimov (American Journals, 2023)
The model of physical education of schoolchildren is considered as a set of forms of physical education united for one purpose and aimed at solving health and educational-pedagogical tasks.
Keywords: Physical development, height, physical education technology, indicators of physical development, coordination abilities, health status of students, indicators of physical development and physical fitness, innovative approach to physical education of schoolchildren.